Developing thinking skills with the use of a module for the concept social organization second year hign shool - Porras, Romeo S. 1939- (1978)
This research paper is a proposed module to develop thinking skills for individualized instruction in the second year high school. The module was prepared in such a way that the students could study a concept in social studies independently or with minimal aid from the teacher. It is based on the Scope and Sequence Chart of the Social Studies for the High School issued by the NSDB-UP Project. The concept involved is social organization for the second year high school. The main focus is on the relationships of the stability of a social institution with role performance and interaction.